Combating Mythology and Changing Reality: the Debate on the Future of Europe - Richard Corbett (Romanian Journal of European Affairs, 2001)
As the enlargement of the EU fuels intense debate on the future of Europe, as a unified, single voiced and hopefully more efficient actor on a global scene, a clear cut assessment of the implications of such processes at national level is needed. As it enlarges its membership, the Union will become a macrocosm of progressively more diverse national interests, which need to dissolve into a unitary and articulated international presence. Against this background, the article looks at the implications of this process, within the framework of the powerful dichotomy federalism-centralism. Indeed, the EU is composed of strong member states with different cultures, which will retain large areas of their own competence; however, the author concludes, they will at the same time play a major role in the EU’s own decision taking, make it an unusually decentralized federation, and not a centralized superstate. In exploring the case of the UK, one of the most prominent actors within the Union which has difficulties coming to terms with its role within a wider Europe, the author attempts to demystify the euro-sceptic legends on Bruxelles taking over power from London and offer an objective overview of the institutions and processes that take place within this decentralized federation. The discussion on the future of Europe, the article concludes, should be translated from diplomatic channels to the citizens’ level, so that “they are at ease” with their union; and this will not be achieved through creating complex new institutions and multi tiered structures, but by objectively assessing, consolidating and improving what was achieved so far.